1998
DOI: 10.1046/j.1440-1703.1998.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of potential PAR on shoot extension in juveniles of the main tree species in a Japanese temperate forest

Abstract: We studied the relationship between potential photosynthetically active radiation (PAR), estimated from hemispherical photographs, and shoot extension rates of juveniles of 12 seral tree species. We distinguished between direct light site factor (DIR), diffuse light site factor (DIF), and gap light index (GLI). We used a log‐linear model to relate growth to DIR, DIF and GLI. Potential PAR explained shoot growth rates significantly in 33 cases out of 36 (12 species × 3 PAR). DIF explained the shoot extension ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…As numerous studies have shown, light environment is one of the most important external factors influencing tree growth (e.g., Canham 1988;Tolvanen 1995;Ishida and Peters 1998;Kawamura and Takeda 2002;Dalling et al 2004). However, for Cleyera japonica, a broad-leaved evergreen woody species, the hierarchical shoot growth according to the branching orders could not be explained only by local light environments (Suzuki 2003): annual shoot length of C. japonica was greater for the lower-order branches when light environments were comparable, although annual shoot length and light environment were positively correlated within same-order branches.…”
Section: Introductionmentioning
confidence: 99%
“…As numerous studies have shown, light environment is one of the most important external factors influencing tree growth (e.g., Canham 1988;Tolvanen 1995;Ishida and Peters 1998;Kawamura and Takeda 2002;Dalling et al 2004). However, for Cleyera japonica, a broad-leaved evergreen woody species, the hierarchical shoot growth according to the branching orders could not be explained only by local light environments (Suzuki 2003): annual shoot length of C. japonica was greater for the lower-order branches when light environments were comparable, although annual shoot length and light environment were positively correlated within same-order branches.…”
Section: Introductionmentioning
confidence: 99%
“…Observações semelhantes foram relatadas por Chandrashekara & Ramakrishnan (1993), em estudo sobre a germinação, estabelecimento e crescimento de plântulas de espécies arbóreas indianas de diferentes estágios sucessionais, dentre elas Actinodaphne malabarica Balakr., classificada como secundária tardia. Similarmente, Ishida & Peters (1998) mostraram haver relação significativa entre a radiação fotossinteticamente ativa (RFA), estimada através de fotografias hemisféricas, e as taxas de crescimento caulinar de 12 espécies arbóreas japonesas, dentre as quais Neolitsea aciculata (Blume) Koidz., tolerante ao sombrea-mento. Adicionalmente, Pinto et al (1993) encontraram que plântulas de Licaria canella (Meissn.)…”
Section: Discussionunclassified
“…King, 1994;Pacala et al, 1994;Ishida and Peters, 1998;Popma and Bongers, 1998) and for trees in environments with relatively high water and nutrient availability (e.g. disturbed forest stands in regions with suffi cient precipitation, including the study site; see below for details), light is often limited due to strong competition among neighboring trees, our fi rst objective is to clarify strategies of P. massoniana and C. lanceolata to cope with low light availability.…”
Section: Introductionmentioning
confidence: 99%